2022
DOI: 10.1371/journal.pmed.1003978
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a therapeutic smartphone application on suicidal ideation in young adults: Findings from a randomized controlled trial in Australia

Abstract: Background Suicidal ideation is a major risk for a suicide attempt in younger people, such that reducing severity of ideation is an important target for suicide prevention. Smartphone applications present a new opportunity for managing ideation in young adults; however, confirmatory evidence for efficacy from randomized trials is lacking. The objective of this study was to assess whether a therapeutic smartphone application (“LifeBuoy”) was superior to an attention-matched control application at reducing the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 42 publications
1
82
0
Order By: Relevance
“…Digital solutions may also be particularly appropriate for expanding adolescent mental health services. Smartphone applications (apps) are one example of how technology can be used to promote adolescent wellness, as aptly illustrated in the accompanying research study in PLOS Medicine by Torok and colleagues, which investigated whether the LifeBuoy app could help reduce the severity of suicidal ideation among young adults [ 3 ]. This study adds to the small but growing body of research demonstrating the potential for novel technologies to transform adolescent mental health service delivery.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Digital solutions may also be particularly appropriate for expanding adolescent mental health services. Smartphone applications (apps) are one example of how technology can be used to promote adolescent wellness, as aptly illustrated in the accompanying research study in PLOS Medicine by Torok and colleagues, which investigated whether the LifeBuoy app could help reduce the severity of suicidal ideation among young adults [ 3 ]. This study adds to the small but growing body of research demonstrating the potential for novel technologies to transform adolescent mental health service delivery.…”
mentioning
confidence: 99%
“…There is increasing evidence to support adolescents’ use of apps for a range of problems, including depression and anxiety [ 8 ], and apps could be a novel way to mitigate the increasing burden of adolescent suicidal behaviors. Torok and colleagues have now shown that apps may be an effective strategy to address suicide risk in young people [ 3 ]. In their randomized controlled trial, Torok and colleagues showed that 6 weeks of engagement with LifeBuoy, a self-guided app based on the principles of dialectical behavior therapy (DBT), led to reduced suicidal ideation among young adults (18 to 25 years old) compared to a visually similar but nontherapeutic control app [ 3 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations